Hubungan Coping Stres dan Dukungan Sosial Dengan Subjective Well Being Siswa Kelas XI Di Sekolah SMA Singosari Deli Tua - Rahmiati Tagore Putri; Lahmuddin Lahmuddin; Nefi Darmayanti (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
The purpose of the research is to determine the relationship of coping stress and social support with subjective well being on the student’ 11 class of Singosari high school Delitua. The sample in this research were taken 100 students. The sampling technique used is Total Sampling Technique. Collected data used is scale, scale of coping stress, scale of social support and scale of subjective well being. Data analysis method used is Multiple regression analysis. The results show that 1). There is a significant positive relationship between coping stress with subjective well being which seen from coeeficient value (Rx1.y) = 0.666 with p = 0.006 0.050, It means there is a positive relationship of coping stress to subjective well being. Subsequently 2). There is a significant positive relationship of social support to subjective well being which seen from the coefficient value (Rx2.y) = 0.374 with p = 0.002 0.050, It means there is positive relationship of social support with subjective well being. 3). There is a significant positive relationship of coping stress and social support with subjective well being seen from linear coefficient value (Rx1.x2.y) = 0.716 with p = 0.002 0.050, It means there is a positive relationship of coping stress and social support with subjective well being.